Nesting habitat of the Tucuman Parrot Amazona tucumana in an old-growth cloud-forest of Argentina - Rivera, Luis (2012)
Tucuman Parrot Amazona tucumana breeds in the cloud-forest of south-eastern Bolivia and north-western Argentina (or Southern Yungas forest). We studied the nesting requirements of the Tucuman Parrot and assessed cavity availability, reuse, and spatial pattern of nests in El Rey National Park-one of the last mature, undisturbed areas of the Southern Yungas forest. We recorded 44 nesting attempts in seven tree species, with most nests (95%) being located in live canopy trees > 60 cm DBH. Most parrot nest-cavities occurred in Blepharocalix salicifolius (60%) and cavities in this species were selected significantly more than expected based on availability. Nests were shallower and higher than nests of other Amazona species. For all years combined, mean nest density of Tucuman Parrot was 0.24 ± 0.04 nest ha-1 and the distance to the nearest active nest was significantly greater than the distance between all trees used as nests. Nesting pairs of Tucuman Parrot were separated by 144.1 ± 152.8 m, while potential nest-trees were 66.0 ± 55.4 m apart. Density of suitable cavities for nesting was 4.6 cavities ha-1. Approximately 16 suitable cavities were available for each breeding pair (0.24 breeding pair ha-1 and four suitable cavities ha-1) and 5% of the suitable cavities available were occupied, suggesting that suitable cavities are not a limiting resource. However, due to the territorial behaviour of breeding pairs, some of these cavities are unavailable to other breeding pairs. The spatial requirements of Tucuman Parrot for nesting could limit management actions intended to increase the density of nesting pairs.